PENERAPAN PEMBELAJARAN AQIDAH AKHLAK BERBASIS BRAINSTORMING PADA KELAS XI MIPA DI MA TERPADU KALIMASADA PLANDAAN JOMBANG: APPLICATION OF BRAINSTORMING-BASED AQIDAH AKHLAK LEARNING IN CLASS XI MIPA AT MA TERPADU KALIMASADA PLANDAAN JOMBANG - Ayuningtiyas, Yolanda; Dzikrul Hakim Al Ghozali, M. (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2023)
This article discusses the application of brainstorming-based Aqidah Akhlak learning in class XI MIPA MA Integrated Kalimasada Plandaan Jombang. The method used in this research is descriptive qualitative method. The results showed that First, the application of brainstorming-based Aqidah Akhlak learning to students at Kalimasada Integrated MA is that students are able to master the material well as evidenced by student learning outcomes in the form of grades. In addition, this method is also able to make students more courageous, creative, independent and tolerant of opinions about a problem that occurs. Second, the obstacles or barriers to the application of brainstorming-based methods in learning Aqidah Akhlak at Kalimasada Integrated MA are: First, students who are less intelligent tend not to be able to capture the material presented. Second, inadequate time allocation. Third, students who are less good at dominating than students who are less good. Fourth, students who tend to be passive rather than active students. Fifth, there is no clear conclusion.